Individual Characteristics and Employee Retention in the Tourism Industry - Ahmad, Nurul Aqilah; Jantan, Amer Hamzah; Manickiam, Neelamehan; Thanasegaran, Ganesh; Sidek, Shafie; Ismail, Kamarulzaman (International Journal of Psychosocial Rehabilitation, 2020)
Recruiting and retaining employees in the tourism industry has been highlighted as the most difficult challenge for organisations. Due to this, high employee turnover rates and challenges on personnel shortage is a constant experience for the Malaysian tourism and hospitality industry. The purpose of this study is to examine the effects of individual characteristics; personal values, competencies and role perceptions as personal factors that influence organisational commitment and retention of employees in Malaysia’s tourism industry. This research intends to affirm the importance and effectiveness of individual characteristics in improving retention amongst employees in the tourism and hospitality industry of Malaysia. Results of this study show that six out of eight hypotheses were supported. The findings show that personal values do not have significant relationships with retention and competencies do not have significant relationships with organisational commitment. However, personal values, competencies and role perception are found to be predictors of employees’ retention mediated by employees’ organisational commitment. The mediator effect of organisational commitment for the relationships between personal values, competencies and role perception; and retention were found to be statistically significant. This study will bring about positive managerial implications where organisations and human resource department are able to utilize the information to practice a better human resource policy.